2014
DOI: 10.1016/j.molmet.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Rictor/mTORC2 facilitates central regulation of energy and glucose homeostasis

Abstract: Insulin signaling in the central nervous system (CNS) regulates energy balance and peripheral glucose homeostasis. Rictor is a key regulatory/structural subunit of the mTORC2 complex and is required for hydrophobic motif site phosphorylation of Akt at serine 473. To examine the contribution of neuronal Rictor/mTORC2 signaling to CNS regulation of energy and glucose homeostasis, we utilized Cre-LoxP technology to generate mice lacking Rictor in all neurons, or in either POMC or AgRP expressing neurons. Rictor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 90 publications
(152 reference statements)
2
64
0
4
Order By: Relevance
“…Thus, disruption of mTORC1 signaling in POMC neurons seemingly affects whole-body energy homeostasis, whereas perturbation of mTORC1 signaling in Agrp neurons does not. Interestingly, similar to mTORC1, Agrp-specific inactivation of mTORC2 signaling, through deletion of rictor, did not result in any alterations in feeding behavior and energy homeostasis, while POMC-specific deletion of rictor caused hyperphagia-induced obesity [30].…”
Section: Discussionmentioning
confidence: 94%
“…Thus, disruption of mTORC1 signaling in POMC neurons seemingly affects whole-body energy homeostasis, whereas perturbation of mTORC1 signaling in Agrp neurons does not. Interestingly, similar to mTORC1, Agrp-specific inactivation of mTORC2 signaling, through deletion of rictor, did not result in any alterations in feeding behavior and energy homeostasis, while POMC-specific deletion of rictor caused hyperphagia-induced obesity [30].…”
Section: Discussionmentioning
confidence: 94%
“…Over the last years, several groups have shown that the mTOR pathway, a signaling node that is highly sensitive to nutritional cues, plays key roles in the regulation of energy balance and glucose metabolism (3,7,9,16,28,29,35). In two recent studies (5, 6), we have demonstrated that DEPTOR, an endogenous inhibitor of mTOR, is widely expressed in the brain, with high levels being found in the MBH.…”
Section: Discussionmentioning
confidence: 94%
“…Activated mTORC1 subsequently activates downstream S6K or inhibits 4E-BP1, resulting in protein translation, cellular proliferation, autophagy, or lipid metabolism. composition and adiposity, impaired glucose tolerance, and insulin sensitivity, indicating that Rictor plays an important role in hypothalamic regulation of energy balance (34). In particular, ablation of Rictor in POMC neurons leads to hyperphagia, obesity, and glucose intolerance, whereas Rictor disruption in AgRP neurons shows no significant changes on energy homeostasis in mice (34).…”
Section: Mtor Signaling and Energy Homeostasismentioning
confidence: 99%
“…composition and adiposity, impaired glucose tolerance, and insulin sensitivity, indicating that Rictor plays an important role in hypothalamic regulation of energy balance (34). In particular, ablation of Rictor in POMC neurons leads to hyperphagia, obesity, and glucose intolerance, whereas Rictor disruption in AgRP neurons shows no significant changes on energy homeostasis in mice (34). Currently, the exact mechanisms underlying these effects of mTORC2 are still largely unknown and require greater investigation.…”
Section: Mtor Signaling and Energy Homeostasismentioning
confidence: 99%